Study of Reasonable Roof Cutting Parameters of Dense-Drilling Roof Cutting and Pressure Relief Self-Forming Roadway in Non-Pillar Mining - Ding Lang; Shuaiming Chen; Hongping Yuan; Jiandong Yu; Yang Yu; Shenghu Luo; Bosheng Hu; Panshi Xie (Applied Sciences)
Roof cutting by dense drilling is one of the main methods of gob-side entry retaining. Taking the 203 working face of the Ruineng Coal Mine as the engineering background, a mechanical model is established to clarify the roof breaking mechanism. Numerical simulation is conducted to analyze the roof cutting effects of different parameters, and reasonable roof cutting parameters are identified. The results show that: ① The increase in roof cutting height is beneficial to roof cutting, but excessive height will cause stress concentration of the ‘key structure’ on the side of the coal pillar. ② It is difficult to cut off the roof when the roof cutting angle is too small, and the cantilever length of the roof increases when the roof cutting angle is too large. ③ The larger the borehole spacing, the smaller the plastic penetration rate between boreholes. The optimal parameters of roof cutting are determined as follows: roof cutting height 8 m; roof cutting angle 15°; aperture size 48 mm; hole spacing at 200 mm. The deformation of the resulting roadway is controllable, indicating that the key parameter determination method is effective.